The role of some job satisfaction factors in marketing performance, from a sample view of the commercial banks in Erbil city - أ.د. عاىػ ضٍػاٌَ٘ ٌ٘ؽعان; م.م. ٌطٍػ ضفَ عي٘فّ ٌطٍػ (QALAAI ZANIST JOURNAL, 2018)
In this research, examine the role of some job satisfaction factors in marketing performance, from a sample view of the commercial banks in Erbil city. Where the extent of the effect of workers identified by a set of factors that cause their satisfaction, which in turn affect their marketing performance. As well as examine the effect of some causal factors of job satisfaction. As an independent variable, which consists of five dimensions as: (relationship with colleagues, the relationship between leaders and subordinates, justice, the desire to keep working, nature of work), in marketing performance as dependent variable which consists of four dimensions (sales growth, market share, profitability, customer satisfaction). Also, to determine the effect of workers in some commercial banks in Erbil city, a set of factors that cause their satisfaction according to their characteristics. However, the descriptive, analytical method used to reach the results of the research. The researchers also prepared a questionnaire for a random sample of some commercial banks that involved (250) staffs. Moreover, the research reached to some results, the most important of which are: the existence of high levels of the two variables, some factors that cause job satisfaction and marketing performance, as well as the existence of relationships and influence between some factors that cause job satisfaction in marketing performance. The researchers recommended maintaining reasonable levels of the variable of some factors causing job satisfaction and marketing performance and the need to invest the strong relationship between some factors that cause job satisfaction and marketing performance at the macro and micro level and guide this relationship towards the success and continuity of banking business.